(untitled) (Pravaha, 2020)
This study is entirely based on secondary sources of data. The data has been collected from the Nepal Stock Exchange (NEPSE). The descriptive and analytical research designs have been used to analyze the sample. The data has-been examined to determine the financial health of Nepalese commercial banks. Financial ratios help in predicting the stock price. The twenty-seven commercial banks are taken as a sample for the study. The information and data has been collected for the year 2065/066. The independent variables earning per share, price earnings ratio, dividend per share, return on equity and book value per share and the dependent variable is market price per share. The financial ratios have been collected from the financial statements of the sample banks and NEPSE. The theoretical framework determines the dependent variable and independent variables. Hence, this event has been used to analyze the financial ratio and variables as independent variables to predict the dependent variable e.g., stock price. In this research five independent variables has been used e.g., price earnings ratio, earning per share, dividend per share, return on equity, and book value per share with the dependent variable e.g., stock Price. The descriptive statistics, correlation analysis and multiple regression models is used to states the impact of independent variables on dependent variable empirically. These models aroused as a strong tool to establish and find if the relationship or correlation exists between the variables. This research also throws light on the ratios can help to predict the stock return for the next period. Results give a clear indication that the P/E Ratio and EPS have the positive impact on the stock price in the NEPSE. The Nepalese investors can rely on the price earnings ratio and the earning per share to predict the market price per share. Hence, the overall conclusion of this research is that the financial variables direct the investors in NEPSE. If the answer is yes investors can rely on P/E ratio and EPS on the confidence level is 99 percent and significance level is below 0.01 which gives clear indication that price earnings ratio and earnings per share may influence the stock price of commercial banks in Nepal.